An examination of the associations between pediatric loss of control eating, anxiety, and body composition in children and adolescents. (August 2018) - Grammer, Anne Claire; Tanofsky-Kraff, Marian; Burke, Natasha L.; Byrne, Meghan E.; Mi, Sarah J.; Jaramillo, Manuela; Shank, Lisa M.; Kelly, Nichole R.; Stojek, Monika M.; Schvey, Natasha A.; Broadney, Miranda M.; Brady, Sheila M.; et al.
Abstract: Background: Data on the link between anxiety and body composition in youth are mixed. Yet, anxiety and disordered eating are highly correlated. One pathway between anxiety and excess body weight and fat mass may be through loss of control (LOC) eating. We examined whether LOC eating mediated the relationship between anxiety and body composition in youth with and without overweight. Method: Non-treatment-seeking youth (8–17 years) participated in studies examining weight and eating behaviors. Anxiety (child- and parent-report of child) and LOC eating were assessed by self-report questionnaires and interviews, respectively. Fat mass was assessed by dual-energy x-ray absorptiometry or air displacement plethysmography. Cross-sectional mediation models with bias-corrected bootstrap confidence intervals (CI) were conducted. Results: 257 youth (12.91 ± 2.76 years; 52.5% female; BMI-z 0.93 ± 1.07) were studied. There was a significant indirect path between child-reported anxiety and both BMI-z (ab = .005, SE = 0.003, 95% CI = 0.001–0.01) and body fat mass (ab = 0.001, SE = 0.001, 95% CI ≤0.001–0.003) through the number of LOC episodes in the past month. No significant indirect paths through the number of LOC episodes was observed for parent-report of child anxiety on BMI-z (ab = 0.004, SE = 0.01, 95% CI = −0.01–0.03) or body fat mass (ab = 0.001, SE = 0.002, 95% CI = −0.002–0.01). No direct paths were observed between anxiety and body composition regardless of the informant. Discussion: LOC eating appears to mediate the relationship of child-reported anxiety with body composition in non-treatment seeking boys and girls. Prospective data are needed to determine if anxiety promotes LOC eating that results in increased risk for excess body weight and fat gain. Highlights: Neither child-report of anxiety nor parent-report of child anxiety was directly related to BMI-z or body fat. Child-report of anxiety was associated with higher BMI-z and greater body fat through loss of control eating. Loss of control eating did not mediate the relationship between parent-report of child anxiety and BMI-z and body fat.